Outcomes in patients with multiple myeloma with TP53 deletion after autologous hematopoietic stem cell transplant. Issue 10 (3rd September 2016) - Gaballa, Sameh; Saliba, Rima M.; Srour, Samer; Lu, Gary; Brammer, Jonathan E.; Shah, Nina; Bashir, Qaiser; Patel, Krina; Bock, Fabian; Parmar, Simrit; Hosing, Chitra; Popat, Uday; et al.
Abstract : TP53 gene deletion is associated with poor outcomes in multiple myeloma (MM). We report the outcomes of patients with MM with and without TP53 deletion who underwent immunomodulatory drug (IMiD) and/or proteasome inhibitor (PI) induction followed by autologous hematopoietic stem cell transplant (auto‐HCT). We identified 34 patients with MM and TP53 deletion who underwent IMiD and/or PI induction followed by auto‐HCT at our institution during 2008–2014. We compared their outcomes with those of control patients ( n = 111) with MM without TP53 deletion. Median age at auto‐HCT was 59 years in the TP53 ‐deletion group and 58 years in the control group ( P = 0.4). Twenty‐one patients (62%) with TP53 deletion and 69 controls (62%) achieved at least partial remission before auto‐HCT ( P = 0.97). Twenty‐three patients (68%) with TP53 deletion and 47 controls (42%) had relapsed disease at auto‐HCT ( P = 0.01). Median progression‐free survival was 8 months for patients with TP53 deletion and 28 months for controls ( P < 0.001). Median overall survival was 21 months for patients with TP53 deletion and 56 months for controls ( P < 0.001). On multivariate analysis of both groups, TP53 deletion (hazard ratio 3.4, 95% confidence interval 1.9–5.8, P < 0.001) and relapsed disease at auto‐HCT (hazard ratio 2.0, 95% confidence interval 1.2–3.4, P = 0.008) were associated with a higher risk of earlier progression. In MM patients treated with PI and/or IMiD drugs, and auto‐HCT, TP53 deletion and relapsed disease at the time of auto‐HCT are independent predictors of progression. Novel approaches should be evaluated in this high‐risk population. Am. J. Hematol. 91:E442–E447, 2016. © 2016 Wiley Periodicals, Inc.